PERAN DIREKTORAT RESERSE KRIMINAL KHUSUS DALAM MENANGGULANGI TINDAK PIDANA PERJUDIAN ONLINE DI WILAYAH KEPOLISIAN DAERAH RIAU - Napitupulu, Yosua Alexander; Erdianto, Erdianto; Andrikasmi, Sukamariko (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
Advances in technology and communication have become increasinglyrapid, affecting every access to human life, In this day and age, crime in thevirtual world (cyber crime). One of the crimes that is currently developing isonline gambling crime. Therefore, the aim of this thesis research is first, to findout the factors that cause the rise of online gambling in the Riau Regional Policearea. Second, to find out the role of the Special Criminal InvestigationDirectorate in dealing with online gambling crimes in the Riau Regional Policearea. Third, to find out the obstacles for the Directorate of Criminal Investigationin tackling online gambling in the Riau Riau Regional Police area.This type of research can be classified as a type of sociological research.This research took place at the Riau Regional Police, where researchersdetermined that the population and sample were all parties related to the problembeing studied. This research uses data sources in the form of primary data andsecondary data, and data collection techniques are carried out by means ofinterviews.From the results of the research and discussions carried out, it can beconcluded that the crime of online gambling in the Riau Regional Police is still sowidespread that it requires maximum efforts, which is caused by various factors,including: First, a preemptive effort in the form of an appeal to online gamblingplayers by conducting outreach in the field of public order. Second, preventiveefforts in the form of blocking sites carried out in collaboration with the Ministryof Communication and Information. Third, repressive efforts can be interpreted ascountermeasures, namely efforts shown to someone who has become evil to helphim return to the right path, by arresting online gambling suspects.Keywords: Law Enforcement – Online Gambling Crime.